Self-compression of two co-propagating laser pulse having relativistic nonlinearity in plasma. (20th November 2017) - Kumar, S.; Gupta, P. K.; Singh, R. K.; Uma, R.; Sharma, R. P.
Abstract: The study proposes a semi-analytical model for the pulse compression of two co-propagating intense laser beams having Gaussian intensity profile in the temporal domain. The high power laser beams create the relativistic nonlinearity during propagation in plasma, which leads to the modification of the refractive index profile. The co-propagating laser beams get self- compressed by virtue of group velocity dispersion and induced nonlinearity. The induced nonlinearity in the plasma broadens the frequency spectrum of the pulse via self-phase modulation, turn to shorter the pulse duration and enhancement of laser beam intensity. The nonlinear Schrodinger equations were set up for co-propagating laser beams in plasmas and have been solved in Matlab by considering paraxial approximation. The propagation characteristics of both laser beams inside plasma are divided into three regions through the critical divider curve, which has been plotted between pulse width τ01 and laser beam power P 01 . Based on the preferred value of critical parameters, these regions are oscillatory compression, oscillatory broadening, and steady broadening. In findings, it is observed that the compression of the laser beam depends on the combined intensity of both beams, plasma density, and initial pulse width.